Mixed localized wave solutions of the Hirota equation. (August 2021) - Liu, De-Yin; Yu, Hui Min
Abstract: In this letter, the mixed localized wave solutions of the Hirota equation are constructed through the modified Darboux transformation. One of them is the mixed 1-breather and 1-rouge wave solution and the other two are the mixed 1-breather and 2-rogue wave solution, and the mixed 2-breather and 1-rogue wave solution. These mixed localized wave solutions are presented graphically by choosing proper parameters and we discuss their dynamic behavior and control briefly.